Mutational changes at HPRT gene locus in type-2 diabetes mellitus - Ghali, Zafir Hassan; Hussein Jamal, Noor (Journal of College of Education, 2021)
Diabetes Mellitus (DM) is a metabolic defects of multiple etiologies characterized by disturbances of protein, fat and carbohydrate metabolism resulting from disorders in insulin secretion, insulin action or both. Studies of mutations at HPRT gene have provide insights into several aspects of somatic mutations in vivo, involving molecular mechanisms of mutagenesis, the relationship between DNA damage and mutation, as well as individual susceptibility factors like DNA repair capacity. In this study, somatic cell genetic marker; Hypoxanthine guanine phosphoribpsyltransferase (HPRT) was examined using short term lymphocyte culture in presence of 6-thioguanine (6-TG) as selective agent for HPRT on peripheral blood lymphocytes taken from twenty five type 2 DM patients using short term lymphocyte culture, their ages ranged between 30-80 years, and 15 healthy people with the same age range as control group.. Resistance to this selective agent refers to as genetic alterations at this HPRT locus. Lymphocytes taken from diabetic patients who were treated with 6-TG shows clear resistance to this analogue. Resistance to 6-TG in those diabetic patients is supported by high frequency of mutations fraction (MF) for those resistant cells. We conclude that type-2 diabetic patients have mutational changes at HPRT gene locus.